Composition of Human Bone Mineral by FTIR and Its Relationship to the Age - Djarwani S. Soejoko; Yessie Widya Sari; Setia Utami Dewi; Nurizati Nurizati; Kiagus Dahlan; Djaja Surya Atmadja (Journal of Medical Physics and Biophysics, 2014)
Deproteinated human bone with hydrazine indicated that percentage of bone mass mineral increased with individual age in the range of child to adult, and then slowly decreased with ageing. Type of bone and sex also influenced the proportional of mineral in bone. Several information was obtained from infrared spectroscopy measurements. Calcium phosphate in bone mineral was a mixture of amorphous calcium phosphates and apatite crystals that rich of carbonates. Most crystals were carbonate apatite type B, with additional small amount of type A and AB. The splitting factor of υ4 phosphate bands indicated that crystalline degree was regulated by age, increases in the range of child to adult, then decrease up to a certain value (0.16) and finally almost constant. It is predicted that apatite crystals that was formed with less calcium phosphate will accompanied by the insertion of crystallization water in order to maintain the constancy of bone volume.